Effectiveness of Psychodrama Model Group Activity Therapy on Anxiety Levels in The Elderly - Saifulah, Dedi; Rellyta, Nova; Saputro, Heri (Griya Eka Sejahtera, 2024)
Background: Psychodrama Model Group Activity Therapy is a therapeutic approach that involves the use of dramatic roles in a group so that individuals can feel some relief. Elderly people often feel anxious because they experience changes due to the aging process. This research was conducted to determine the effectiveness of psychodrama model group activity therapy on anxiety levels in the elderly at UPT PSTW Tulungagung.Method: This research uses a pre-experimental design with one group pretest-posttest type. With purposive sampling technique, a sample of 30 respondents was obtained. Using the Geriatric Anxiety Scale questionnaire instrument. Data analysis used the Wilcoxon statistical test.Results: The results of the research from 30 respondents after carrying out psychodrama model activity therapy showed that there were 2 (6.7%) respondents with severe anxiety, 16 (53.3%) respondents with moderate anxiety, 10 (33.3%) respondents with mild anxiety, and the elderly who did not experience anxiety were 2 (6.7%) respondents. Analysis of the Wilcoxon statistical test showed that the